The characterisation and provenance of crude oils stranded on the South Australian coastline. Part II: Potential parent petroleum systems. (October 2021) - Corrick, Alexander J.; Hall, Philip A.; Gong, Se; McKirdy, David M.; Trefry, Christine; Ross, Andrew S.
Abstract: In 2014–2016 more than 600 specimens of semi-solid crude oil were recovered from 30 ocean beaches along the coastline of South Australia, as part of the recently completed Great Australian Bight Research Program. All are believed to be products of submarine oil seepage. Their source-specific biomarker signatures provide the basis for their assignment to sixteen oil families, some previously unrecognised. Two of these families (asphaltite and asphaltic tar) likely originated from Cretaceous marine source rocks in the offshore Bight Basin. The others comprise waxy oils of lacustrine, fluvio-deltaic and marine source affinity. Their biomarker characteristics do not match those of any Australian crude oil. However, they are strikingly similar to those of oils found in Cenozoic and Mesozoic basins throughout the Indonesian Archipelago and elsewhere in Southeast Asia. Highlights: Asphaltic oils and waxy tar balls from 30 South Australian beaches analysed by GC–MS. Alkane biomarker signatures of 127 specimens distinguish 16 different oil families. Two marine asphaltic oils are indicators of offshore seepage in the Bight Basin. Various waxy oils are products of multiple petroleum systems throughout SE Asia.